2022
DOI: 10.37796/2211-8039.1308
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor Receptor 1-Bound Extracellular Vesicle as Novel Therapy for Osteoarthritis

Abstract: Osteoarthritis (OA) is a joint condition that causes significant impairment of the chondrocyte. The gradual degradation of the cartilage lining of one or more freely moving joints, as well as persistent inflammation, are the causes of osteoarthritis. Current medications focus on alleviating symptoms rather than curing the condition. The aim of this review is to evaluate the potential use of fibroblast growth factor receptor 1-bound extracellular vesicle as novel therapy for osteoarthritis. This review article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…Numerous proinflammatory mediators are produced during the progression of OA, including IL-1β and TNF-α, leading to the activation of catabolic factors, resulting in cartilage degradation and bone erosion [36,37]. The levels of IL-1β and TNF-α expression in serum and synovial tissue are associated with the pathological process of OA [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous proinflammatory mediators are produced during the progression of OA, including IL-1β and TNF-α, leading to the activation of catabolic factors, resulting in cartilage degradation and bone erosion [36,37]. The levels of IL-1β and TNF-α expression in serum and synovial tissue are associated with the pathological process of OA [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Although all four FGFRs are encoded by different genes, their amino acid sequences share 56–71% similarity. Hypertrophic chondrocytes mainly express FGFR-1 and FGFR-2 and participate in intramembrane osteogenesis [ 94 , 95 ]. Osteoblasts in the ossification center mainly express FGFR-2 [ 96 ] and a small amount of FGFR-1 and FGFR-3 [ 97 ].…”
Section: Bone Growth Factorsmentioning
confidence: 99%
“…EV therapies may be a promising treatment for OA in peripheral joints and TMJ because of their low immunogenicity, low cytotoxicity, and long-term stability characteristics. Recently, the EVs from modified cells or loaded with drugs showed therapeutic effects in OA ( 182 , 186 , 187 ), which are attractive for this field. There are three forms of EVs, and the recent research of EV therapy mainly focused on exosomes, which showed therapeutic effects in OA treatment ( 188 ).…”
Section: Conclusion and Perspectivementioning
confidence: 99%